KONSEP TAWASSUL DAN KUMPULAN DO’A DALAM KITAB RISALAH NURANIYYAH: (STUDI KITAB RISALAH NURANIYYAH KARYA SYEKH MUHAMMAD ZAINI AL-BANJARI) - Zubaidah (An-Nahdhah | Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2023)
Tawassul is a practice carried out by Rasulullah SAW, his friends, past Ahlussunnah scholars until now. The Risale Nuraniyyah Book is a book written by His Excellency Sheikh Muhammad Zaini Al-Banjari. Risalah Nuraniyyah is an explanation of one of the tawassul written by Sheikh Samman. Apart from containing explanations of tawassul sammaniyyah, this book also includes several written prayers interspersing the discussion. Based on the data to be collected, this type of research is library research. The subject of this research is the Risalah Nuraniyyah book. Meanwhile, the object itself is the Tawassul Concept and Collection of Prayers. The results of this research state that the ability of tawassul has been explained by the Al-Qur'an, Al-Hadith, and the atsar of the Ulama. There are 16 prayers listed in the Risalah NuraniyyahI book, which are quoted based on their relevance to the material being discussed.